Sosialisasi Pengenalan dan Pemanfaatan Teknologi Artificial Intelligence (AI) untuk Memberdayakan Masyarakat Samo Gane Barat, Kabupaten Halmahera Selatan - Syarifuddin N. Kapita; Amal Khairan; Alfanugrah A. Hi. Usman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Limited knowledge and utilization of digital technology in the fisheries and plantation sectors remains a major obstacle for the people of Samo Village, South Halmahera Regency, the majority of whom work as fishermen and farmers. This results in low productivity, limited access to information, and less than optimal development of micro-enterprises based on local potential. This community service activity aims to introduce and train the use of Fishbrain, Plantix, and ChatGPT applications relevant to local community needs. The activity implementation method includes three main stages: the preparation phase, which involves coordination with village officials and the development of training materials; the implementation phase, which involves socialization and hands-on training; and the evaluation phase, which involves discussions, reflections, and Q&A sessions with participants. The results of the activity demonstrated a significant increase in participants' understanding and skills in utilizing digital technology. The Fishbrain application has been proven to assist fishermen in determining more potential fishing locations based on global community data, while Plantix is ​​useful in detecting plant diseases, providing treatment recommendations, and increasing crop yields. Meanwhile, ChatGPT is used by the community as a virtual assistant to support information searches, innovation ideas, product marketing strategies, and digital-based small business planning. The participants' enthusiasm was evident in their active involvement throughout the training, their eagerness to try the applications independently, and their ability to repeat the three applications' core functions. In conclusion, this training activity not only broadened the community's digital knowledge and skills but also encouraged a shift in mindset toward utilizing technology as a means to improve well-being. With the knowledge gained, the Samo Village community is expected to be more adaptive to technological developments, enabling the sustainable development of the fisheries, plantations, and local micro-enterprises sectors.